ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PADA PT BANK TABUNGAN PENSIUNAN NASIONAL (BTPN) - MARPAUNG, FEBE APRILIA; MANOPPO, WILFRED S.; KELES, DANTJE (JURNAL ADMINISTRASI BISNIS (JAB), 2016)
Abstract. This study aims to assess the financial performance of the Bank BTPN is reviewed based on liquidity ratios, profitability ratios, and the risk ratio of bank operations for the period 2013-2015. This study used quantitative descriptive analysis with ratio analysis approach. Source of data derived from the annual financial statements of Bank BTPN year period 2013-2015. The results showed the company's financial performance ups and downs. However, in general the financial performance of the Bank BPTN good enough. Therefore, the leadership of the Bank's need to continue maintaining the sustainability of financial performance by doing the good governance of the business activities. Keywords: Liquidity, Profitability, Business Risk Bank